Analyzing the Scientific Trends and Effects of Sports Studies And Sponsorship: A Bibliometric Assessment of a Prominent Journal - Erfan Moradi; Ashraf ELmidani (Sports Business Journal)
Purpose: This study explores emerging sports marketing and sponsorship research trends by examining theoretical, thematic, and methodological frameworks across time. Articles were classified based on their relevance to the evolution of sport business industry segments, conceptual, intellectual, and social structures, and their citation patterns.Methodology: The investigation employs a multi-method analytical approach, focusing on research articles published in the prominent International Journal of Sports Marketing and Sponsorship (IJSMS) from 2016 to 2023. Using R software, data were obtained from Scopus and subjected to bibliometric analysis to elucidate scholarly contributions and thematic evolution over time.Findings: The findings indicated that a significant portion of the articles in the paradigm funnel classification were based on experimental observations and analytical methods. The topics covered ranged from sustainability and social media to esports, Twitter, football fans, loyalty, and spectators. Additionally, there was a focus on relationship marketing and service quality as emerging themes. Additionally, the use of quantitative methods, empirical observations, and analytical methods, and the involvement of multiple authors and longer article titles positively impacted article citations.Originality: This research will serve as a valuable roadmap for researchers in sport marketing and sponsorship. Additionally, scholars will be able to discern how articles on a particular topic have evolved through this research. This research offers valuable insights into the evolution of sport marketing and sponsorship research, providing scholars with guidance for future research directions by highlighting historical gaps and niche areas. This comprehensive historical review maps the significant themes in sport marketing and sponsorship research and sheds light on the academic trends that have shaped the field. The findings can help guide scholars toward historically underexplored areas in the literature, aiding in the continued development of the field. While the study highlights key areas such as consumer behavior, sports marketing strategy, and service quality, there remains a lack of focus on interdisciplinary approaches combining sport marketing with emerging fields like sustainability, digital innovation, and social equity. Future research should investigate how advanced technologies, such as blockchain, AI, and the metaverse, reshape fan engagement and sponsorship strategies. Additionally, researchers could examine the role of sport sponsorships in promoting social equity, diversity, and inclusion, primarily through campaigns that address societal challenges or empower marginalized groups.